Rankings over Time. (1st September 2016) - Jones, Michael A.; Webb, Alexander; Wilson, Jennifer
Summary: In 2010, Kim Clijsters won the U.S. Open but had her world ranking drop from #3 to #5 by the Women′s Tennis Assocation (WTA). How can a tennis player win a tournament but drop in the rankings? The WTA uses a moving window to determine the rankings. Discounting older results in the window can prevent such counterintuitive behavior. We consider geometric and arithmetic discounting methods. We examine real data from the WTA and comment on discounting methods already in use by the Fédération Internationale de Football Association (FIFA) for ranking national teams for the World Cup and the Official World Golf Rankings.